Improving the Translational Medicine Process: Moving Patients From “End-Users” to “Engaged Collaborators” - Battaglia, Manuela; Furlong, Pat; Wulffraat, Nico Martinus; Bellutti Enders, Felicitas (Frontiers in Medicine, 2019)
Translational medicine works through the definition of unmet medical needs, their understanding and final resolution. In this complex and multi-disciplinary process patients have always been regarded as “end-users” or no more than “data provider”. Considering that the translational practice is nowadays highly inefficient (i.e., large intellectual and economical resources are wasted with limited impact on people health) here we propose to reverse the process: start from patients, engage them and keep them at the center. A new partnership needs to be formed between the patients and the health care professionals, as well as the treating physicians, to make the most out of the current “health resources”. New patient-centric approaches are emerging but they remain isolated phenomena often difficult to implement. Here - with this perspective - we aim at thinking differently and learning from new experiences. We will discuss new approaches to create a radical change in the way translational medicine is managed and how this change would significantly impact people health and health care systems.